Helipot Analog to Digital Microcircuit Model 866 with razor - Armstrong & Hess (1950)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products, in this case a pair of analog to digital (ADC) converters.
Keywords: Microelectronics; Analog-to-digital converters; Beckman Instruments, Inc.